2019
DOI: 10.1088/1361-648x/aafd06
|View full text |Cite
|
Sign up to set email alerts
|

Magneto-optical properties of Au upon the injection of hot spin-polarized electrons across Fe/Au(0 0 1) interfaces

Abstract: We demonstrate a novel method for the excitation of sizable magneto-optical effects in Au by means of the laser-induced injection of hot spin-polarized electrons in Au/Fe/MgO(001) heterostructures. It is based on the energy-and spin-dependent electron transmittance of Fe/Au interface which acts as a spin filter for non-thermalized electrons optically excited in Fe. We show that after crossing the interface, majority electrons propagate through the Au layer with the velocity on the order of 1 nm/fs (close to th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 59 publications
0
20
0
Order By: Relevance
“…Recent time-resolved experiments 17 19 have demonstrated the detection of spin injection using the linear, complex and second harmonic magneto-optic Kerr effect (SHMOKE). The authors of 18 , 19 observed the generation of non-thermal spin transport, as predicted theoretically 20 22 . SHMOKE is sensitive to spin polarization at interfaces and is therefore well suited for observing transport effects.…”
Section: Introductionmentioning
confidence: 60%
See 1 more Smart Citation
“…Recent time-resolved experiments 17 19 have demonstrated the detection of spin injection using the linear, complex and second harmonic magneto-optic Kerr effect (SHMOKE). The authors of 18 , 19 observed the generation of non-thermal spin transport, as predicted theoretically 20 22 . SHMOKE is sensitive to spin polarization at interfaces and is therefore well suited for observing transport effects.…”
Section: Introductionmentioning
confidence: 60%
“…The sign of the injected spin polarization for delay times fs is consistent with several theoretical predictions 20 22 , 36 . However, for delay times fs, several authors observed the injection of minority spins into the gold layer 18 , 21 . This negative polarization shortly after the excitation pulse is not present in our data.…”
Section: Resultsmentioning
confidence: 99%
“…By adding the damping term and the explicit expression for A (n) 32 from Eq. (27) we arrive at the most important analytical equation in this paper:…”
Section: Magnetization Dynamics Excited By Acoustic Pulsesmentioning
confidence: 99%
“…Depending on a mechanism, magnetization dynamics induced by a femtosecond laser pulse can be sorted into the following categories: (i) thermal effects [3,13], (ii) magnetooptical effects [22], (iii) magnetoacoustic effects [15,18,19,[23][24][25][26][27] and (iv) spin transfer torque [28][29][30][31]. Despite of the facts that the spin transfer torque is an efficient mechanism to drive coherent magnetization dynamics in ferromagnet through ultrashort pulses of spinpolarized electrons propagating in noble metals for several tens of nanometers before they lose their spin polarization [32], acoustic pulses can propagate over much larger distances before they vanish. Picosecond acoustic pulses generated by femtosecond laser excitations [25,[33][34][35] can drive the small-angle precession of ferromagnetic resonance (FMR) in various ferromagnetic samples [15,19,23,24].…”
Section: Introductionmentioning
confidence: 99%
“…An example of this is the qualitative discrepancy between the results obtained by different optical techniques in spin-transport experiments. 1 The desire to gain insight into the spin-resolved band structure has driven the development of detection schemes that allow the recording of the emitted electron energy, momentum, and spin.…”
Section: Introductionmentioning
confidence: 99%